Generational Income Mobility: A Review Essay - Piraino, Patrizio; Haveman, Robert (My University, 2006)
This essay discusses studies collected by Miles Corak that examine changes in economic status from one generation to the next. The essays cover 15 countries, 10 of them North American or European.